2013
DOI: 10.1074/jbc.m112.395939
|View full text |Cite
|
Sign up to set email alerts
|

Critical Hydrogen Bond Formation for Activation of the Angiotensin II Type 1 Receptor

Abstract: Background:The N111G and N111W mutations make the AT 1 receptor constitutively active and inactivable, respectively. Results: The orientation and interactions of D74 2.50 are influenced by the residue at position 111 3.35 . Conclusion: H-bond formation between D742.50 and N46 1.50 is critical for AT 1 receptor activation. Significance: This novel molecular switch could be involved in the GPCR activation mechanism as it involves highly conserved residues D 2.50 and N 1.50 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 74 publications
3
34
0
1
Order By: Relevance
“…Since mutations of either Asn111 TM3 or Asn295 TM7 induce constitutive activation of the AT1R, the inactive conformation of AT1R was proposed to be stabilized by the H-bond between Asn111 TM3 and Asn295 TM7 , which is confirmed by the crystal structure (Zhang et al, 2015 (Cabana et al, 2013;Zhang et al, 2015). Thus, the network of interacting residues around Asn111 TM3 and Asn295…”
Section: Tm7supporting
confidence: 54%
See 2 more Smart Citations
“…Since mutations of either Asn111 TM3 or Asn295 TM7 induce constitutive activation of the AT1R, the inactive conformation of AT1R was proposed to be stabilized by the H-bond between Asn111 TM3 and Asn295 TM7 , which is confirmed by the crystal structure (Zhang et al, 2015 (Cabana et al, 2013;Zhang et al, 2015). Thus, the network of interacting residues around Asn111 TM3 and Asn295…”
Section: Tm7supporting
confidence: 54%
“…Furthermore, direct structure-function studies on the AT1R have suggested both rotational and translational motion of TM2, TM3, TM5, TM6, and TM7 in the N111G-AT1R (Boucard et al, 2003;Martin et al, 2004Martin et al, , 2007Domazet et al, 2009). Based on molecular dynamics simulation studies on N111G-AT1R, an active-state H-bond network where Asp74 TM2 interacts with Asn46 TM1 and Asn295 TM7 was proposed (Cabana et al, 2013). The same authors also indicated that the N111G mutation leads to hydrating the hydrophobic core and facilitating the interaction of the toggle switch residue, Trp253 TM6 with Ala291 TM7 and Leu112 TM3 (Cabana et al, 2013).…”
Section: Molecular Mechanism Of Inverse Agonism Of At1r Blockersmentioning
confidence: 99%
See 1 more Smart Citation
“…Of particular interest is a region within the receptor identified as the major H-bond network (MHN). It is composed of several functionally important and conserved polar residues among class A GPCRs (8,9). This region has also been identified as a sodiumbinding site in some GPCRs (10,11).…”
mentioning
confidence: 99%
“…Nowadays, the latest breakthroughs in molecular dynamics simulations deal with biological processes that take place over longer timescales. For example, protein folding [18], transmembrane receptor activation [19,20] and ligand binding [21]. These simulations require substantial computer power or purpose built hardware such as Anton that pushes the current limit of MD simulations to the millisecond range [22].…”
Section: Introductionmentioning
confidence: 99%